ANALISA RESPON SPEKTRA GEMPA DI PERMUKAAN BERDASARKAN PENDEKATAN SITE SPECIFIC ANALYSIS - Renata A. Wijaya; Bianca Febriani; Windu Partono; Rudi Yuniarto Adi (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
SNI 03-1726-2002 mentions that the seismic requirements for building construction design should be based on 4 accelerograms from 4 different earthquake events. One of them is El Centro (California, 1940). In 2010, Indonesian Earthquake revision team defined a new seismic hazard maps. Those efforts have led to revisalSNI 03-1726-2002, because after 2002, there was earthquakes, whose magnitude was bigger than the estimation before. This study will analyze the spectrum response that will be showed through maps of amplification factor distribution and acceleration spectrum on Semarang city area. From those maps, amplification factor value of El Centro earthquake will be compared to the others (Hector Mine, Kobe, and Loma Prieta). Also the comparison of acceleration spectrum value ( PGA, T=0.2, T=1) that caused by Earthquake El Centro and the others. The last is the comparison of spectrum response that was the result of this study and the spectrum response from SNI 03-1726-2002.